Hubungan Perhatian Orang Tua dan Motivasi Belajar Dengan Hasil Belajar Siswa - Sulistiawati Apriani; Khairun Nisa; Husniati Husniati (Journal of Classroom Action Research, 2022)
This study aims to find out the relationship between parental attention and learning motivation and student learning outcomes. This research is a quantitative study with correlational analysis techniques. The population in this study amounted to 326 students of class V SDN Cluster I Ampenan. Sampling was conducted using the Proportionate Stratified Random Sampling technique with a research sample of 179 students. The data collection techniques in this study used questionnaires and documentation. The analysis prerequisite test uses the normality test, the homogeneity test, and the linearity test. After normal, homogeneous, and linear data then continued with product-moment correlation analysis and double correlation. Based on the results of the study showed that: (1) there is no relationship between parental attention and the learning outcomes of students of class V SDN Cluster I Ampenan. This is evidenced by the results of the product-moment correlation analysis obtained the value of r_hitung = 0.097 lower than r_tabel = 0.146 at the level of significance of 5%. (2) There is no relationship between learning motivation and the learning outcomes of students of class V SDN Cluster I Ampenan. This is evidenced by the results of the product-moment correlation analysis obtained the value of r_hitung = 0.054 lower than r_tabel = 0.146 at the level of significance of 5%. (3) There is no relationship between parental attention and learning motivation and the learning outcomes of students of class V SDN Cluster I Ampenan. This is evidenced from the results of the double correlation analysis obtained F change value = 0.431 > 0.05 then it can be concluded that the variables of parental attention and motivation to learn simultaneously have no relationship with the learning outcomes of students of class V SDN Group I Ampenan